Returning to haemodialysis after kidney allograft failure: a survival study with propensity score matching. Issue 4 (19th July 2018) - Varas, Javier; Pérez-Sáez, María José; Ramos, Rosa; Merello, Jose Ignacio; de Francisco, Angel Luis M; Luño, José; Praga, Manuel; Aljama, Pedro; Pascual, Julio
Abstract: Background: Patients who return to dialysis after kidney allograft failure (KAF) are classically considered to have lower survival rates than their transplant-naïve incident dialysis counterparts. However, this observation in previous comparisons could be due to poor matching between the two populations. Methods: To compare survival rates between patients who returned to haemodialysis (HD) after KAF versus transplant-naïve incident HD patients, we performed a retrospective study using the EuCliD ® database (European Clinical Database) that collects data from Fresenius Medical Care (FMC) outpatient HD facilities in Spain. Propensity score matching (PSM) was performed to homogenize both populations. Results: This study included 5216 patients from 65 different FMC clinics between 2009 and 2014. Naïve incident HD patients were mostly male, older, comorbid and more commonly had catheters as vascular access. During the study follow-up, 3915 patients exited, of whom 1534 died. The mean survival time for the entire cohort was 4.86 years [95% confidence interval (CI) 4.78–4.94]. Univariate Cox analysis indicated higher mortality risk among transplant-naïve incident HD patients [hazard ratio (HR) 1.728; 95% CI 1.35–2.21; P < 0.001). However, this difference was no longer significant after multivariate adjustment. After applying PSM to minimize the bias due to indication issue, we obtained an adjusted population composed of 480 naïve and 240 KAF patients. The results analysing the PSM-adjusted cohort confirmed similar survival in both cohorts (log-rank, 3.34; P = 0.068; HR 1.382; 95% CI 0.97–1.95; P = 0.069). Conclusions: When comparing properly matched patient groups, patients who return to HD after KAF present similar survival than survival than transplant-naïve incident patients.